Analisis Pengaruh Jumlah Likes Terhadap Jumlah Viewers Konten Di Akun Tiktok PT Nugraha Kreasi Digital Menggunakan Metode Regresi Linear - Lufita alvira; Hermanto (Jurnal Sains Informatika Terapan, 2026)
The rapid growth of social media, particularly TikTok, has opened significant opportunities in digital marketing strategies. This research is motivated by the lack of data-driven analysis regarding the influence of user interaction on the reach of TikTok content on the official account of PT Anugrah Kreasi Digital. The main focus of this study is to analyze the effect of the number of likes on the number of viewers of the company's TikTok content. The study uses a quantitative approach with a simple linear regression method implemented using the Python programming language on the Google Colaboratory platform. The dataset consists of 100 TikTok contents manually collected from the company's official account, with the main variables being the number of likes and the number of viewers. The analysis process includes data exploration, visualization, training and testing data splitting, model building, and evaluation using Mean Squared Error (MSE) and the coefficient of determination (R²). The results show that the number of likes has a positive effect on the number of viewers, with an R² value of 0.665 and a regression coefficient (β₁) of 14.817. This means that each additional like is estimated to increase the number of viewers by approximately ±14.8. These findings provide a strong analytical foundation for the company to evaluate and develop more effective and data-driven TikTok content strategies.